(untitled) (Iranian Journal of Kidney Diseases, 2015)
Endoplasmic reticulum produces folds and exports proteins. There are studies showing the role of endoplasmic reticulum in pathogenesis of diabetic complications including diabetic nephropathy. This article reviews the pathophysiology associated with the role of endoplasmic reticulum in diabetic nephropathy and the therapeutic aspects of this finding.